2023
DOI: 10.1155/2023/6272743
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Body Circumference Determinants for Hand Grip Strength: A Population-Based Mon-Timeline Study

Agiimaa Byambaa,
Indra Altankhuyag,
Otgonbayar Damdinbazar
et al.

Abstract: Background. Hand grip strength (HGS) is a tool for diagnosing sarcopenia. In this study, we examined some anthropometric and body circumference measurements as determinants for HGS. Methods. This cross-sectional study was conducted with participants (Mongolians, n = 1080, aged 18–70, mean age of 41.2 ± 13.9 years, 33.7% of men) from the “Mon-Timeline” cohort study. To measure HGS, a digital grip strength dynamometer was used. Results. Mean HGS in men was 40.1 ± 10.4 kg and in women was 24.5 ± 5.6 kg. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There are many studies which evaluated the association between HGS and height or weight. Byambaa found that HGS was significantly related with height, not weight [17]. The report of Ong also confirmed that HGS was significantly positively associated with height [18].…”
Section: Hand Grip Strength and Anthropometric Variablesmentioning
confidence: 67%
“…There are many studies which evaluated the association between HGS and height or weight. Byambaa found that HGS was significantly related with height, not weight [17]. The report of Ong also confirmed that HGS was significantly positively associated with height [18].…”
Section: Hand Grip Strength and Anthropometric Variablesmentioning
confidence: 67%